Do Humor Styles of Patients Affect Their Intensive Care Experiences? - Aktura, Seher Çevik; Sarıtaş, Serdar; Tarlacı, Sultan (Karyay Karadeniz Yayımcılık Ve Organizasyon Ticaret Limited Şirketi, 2022)
The study was conducted in order to examine the correlation between the humor styles of the patients and their intensive care experiences. This study was conducted in descriptive and correlational design. The population of the study consisted of the patients who were treated in the general surgery, neurosurgery, neurology, and organ transplantation intensive care units of a university hospital. Its sample consisted of 204 intensive care patients. The data were collected using the Personal Information Form prepared by the researchers, Humor Styles Questionnaire, and Intensive Care Experience Questionnaire. The descriptive statistics, independent samples t test, One Way ANOVA, post-hoc tests, Correlation analysis and Cronbach's Alpha reliability analysis test were used to assess the data. In the study, it was found that the intensive care patients mostly used the affiliative and aggressive humor style and they had a positive intensive care experience. Additionally, there were a positive significant weak correlation between the affiliative humor and the subscale of “satisfaction with care” of ICEQ and a negative significant weak correlation between the subscales of “frightening experiences” and “recall of experience”. As a result of the study, it was observed that the patients using the affiliative humor style had less pessimistic experience, remembered the intensive care experiences less, and were satisfied with the care provided the intensive care unit.
Keywords: Nursing; Hemşirelik